SWITCHING BLOOD GLUCOSE CONTROL SYSTEM EXECUTION WITHOUT INTERRUPTION OF THERAPY DELIVERY (2021)
Systems and methods are disclosed herein for switching control of an ambulatory medical device from an application executing on the ambulatory medical device to a safe version or a new version of the application without interrupting therapy provided by the ambulatory medical device to a subject. The ambulatory medical device can maintain copies of a safe version and a new version of the application. The disclosed systems and methods can execute the new version, while the prior version of the application continues to execute, determine whether a minimum set of operating conditions are satisfied by the new version, and switch control of the ambulatory medical device from the prior version to the new version. The systems and methods can also automatically revert to the safe version of the application case the current version is malfunctioning without interrupting therapy provided to the subject.